2016
DOI: 10.1002/elan.201600252
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Fast and Sensitive Nanostructure Voltammetric Sensor for Determination of Curcumin in the Presence of Vitamin B9 in Food Samples

Abstract: 1Introduction Keywords: Curcumin · Vitamin B 9 · Cadmium oxide nanoparticles · Voltammetric sensor · Modified electrode [a] S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Also, a plot of peak height (Ip) vs. the square root of scan rate (v 1/2 ) was found to be linear in the wide range of 20-300 mV/s. As depicted in Figure 4, a plot of log peak current with log scan rate gives a linear relationship with a slope of 0.437; This value close to the theoretical value of 0.5, indicates that the electrochemical oxidation of mirtazapine is controlled by diffusion processes [34].…”
Section: Effect Of Scan Ratesupporting
confidence: 74%
“…Also, a plot of peak height (Ip) vs. the square root of scan rate (v 1/2 ) was found to be linear in the wide range of 20-300 mV/s. As depicted in Figure 4, a plot of log peak current with log scan rate gives a linear relationship with a slope of 0.437; This value close to the theoretical value of 0.5, indicates that the electrochemical oxidation of mirtazapine is controlled by diffusion processes [34].…”
Section: Effect Of Scan Ratesupporting
confidence: 74%
“…As depict in Figure S1, the oxidation peak current of SOT is linearly correlated with scan rates; I p (μA)=−20 μA+10.241 μA/(Vs −1 ) 1/2 ; R 2 =0.9990. This behaviour indicates that, the electrochemical oxidation of SOT is controlled by diffusion processes .…”
Section: Resultsmentioning
confidence: 99%
“…With the scan rates, the peak potential of the cathodic peak at −0.60 V shifted to a negative potential with increasing the scan rates. This behavior showed that the reduction reaction is irreversible .…”
Section: Resultsmentioning
confidence: 99%